Legislative Bellwethers: The Role of Committee Membership in Parliamentary Debate. Issue 2 (2nd November 2018) - Fernandes, Jorge M.; Goplerud, Max; Won, Miguel
Abstract : Political parties and legislators use legislative debates to establish their reputation, challenge rivals, and engage in coalition management, among many other tasks. Yet, existing theories on parliamentary debates have abstracted away from the need for information and expertise, which are costly to acquire. Drawing on the "informational" perspective on legislative organization, we address this problem by arguing that party leaders use committees as training arenas for their backbenchers. They task their assigned members with acquiring specific expertise and then rely heavily on those members during the corresponding debates. We turn to the Portuguese legislature, from 2000 to 2015, to discuss how saliency, government dynamics, and party size affect the use of experts. We test this theory using a novel approach to classify speeches that leverages the texts of legislation as training data for a supervised approach.